The Extraction Socket Management Continuum: A Hierarchical Approach to Dental Implant Site Development. Issue 2 (1st November 2018) - Cheng, Albert W.; Berridge, Joshua P.; McGary, Ryan T.; Erley, Kenneth J.; Johnson, Thomas M.
Abstract : Focused Clinical Question: How should clinicians manage dental extraction sockets when immediate implant placement is contraindicated, and alveolar ridge preservation is expected to result in inadequate bone volume for implant placement? Summary: Three fundamental options for extraction socket management form a hierarchical continuum in sites where dental implant placement is planned: place an immediate implant, perform ridge preservation, or perform ridge augmentation. The available volume and quality of bone and keratinized mucosa are the primary considerations driving the decision, and each tier in the continuum encompasses a variety of techniques with attendant advantages and disadvantages. Conclusions: Some immediate implant protocols require no mucoperiosteal flap and possibly produce the most favorable clinical and patient‐centered outcomes compared with other extraction socket management approaches. Conversely, guided bone regeneration at dental extraction sites can result in substantial gains in alveolar ridge dimensions, although this treatment may adversely influence mucosal architecture and carry increased risk of postoperative morbidity. When favorable bone and mucosa are present at a dental extraction site, immediate implant placement may be the treatment of choice, barring unusual circumstances. Ridge preservation, typically associated with minimal postoperative morbidity, is a rational second choice when acceptable ridge dimensions are anticipated after healing.